Experiences and perspectives of older people regarding advance care planning: A meta-synthesis of qualitative studies. (May 2017) - Ke, Li-Shan; Huang, Xiaoyan; Hu, Wen-Yu; O'Connor, Margaret; Lee, Susan
Background: Studies have indicated that family members or health professionals may not know or predict their older relatives' or patients' health preferences. Although advance care planning is encouraged for older people to prepare end-of-life care, it is still challenging. Aim: To understand the experiences and perspectives of older people regarding advance care planning. Design: A systematic review of qualitative studies and meta-synthesis was conducted. Data sources: CINAHL, MEDLINE, EMBASE, and PsycINFO databases were searched. Results: A total of 50 articles were critically appraised and a thematic synthesis was undertaken. Four themes were identified: life versus death, internal versus external, benefits versus burdens, and controlling versus being controlled. The view of life and death influenced older people's willingness to discuss their future. The characteristics, experiences, health status, family relationship, and available resources also affected their plans of advance care planning. Older people needed to balance the benefits and burdens of advance care planning, and then judge their own ability to make decisions about end-of-life care. Conclusion: Older people's perspectives and experiences of advance care planning were varied and often conflicted; cultural differences amplified variances among older people. Truthful information, available resources, and family support are needed to enable older people to maintain dignity at the end of life. The views of life and death for older people from different cultures should be compared to assist health professionals to understand older people's attitudes toward advance care planning, and thus to develop appropriate strategies to promote advance care planning in different cultures.